2001
DOI: 10.1182/blood.v97.4.1056
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-mediated constitutive expression of SOCS-3 in cutaneous T-cell lymphoma

Abstract: A characteristic feature of neoplastic transformation is the loss of external control by cytokines and extracellular matrix of cellular differentiation, migration, and mitogenesis. Because suppressors of cytokine signaling (SOCS) proteins are negative regulators of cytokine-induced signaling, it has been hypothesized that an aberrant SOCS expression plays a role in neoplastic transformation. This study reports on a constitutive SOCS-3 expression in cutaneous T-cell lymphoma (CTCL) cell lines. SOCS-3 protein is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 36 publications
7
83
1
1
Order By: Relevance
“…Our data supports previous studies demonstrating constitutive expression of STAT3 in CTCL cell lines, [10][11][12][13][14][15][16][17][18][19] and confirm findings in a recent report that showed constitutive and sustained ex vivo expression of pSTAT3 over 24 h in PBMCs from a group of four SS/MF patients. 18 In contrast, an earlier study documented strong expression of pSTAT3 in only 2 out of 14 SS patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our data supports previous studies demonstrating constitutive expression of STAT3 in CTCL cell lines, [10][11][12][13][14][15][16][17][18][19] and confirm findings in a recent report that showed constitutive and sustained ex vivo expression of pSTAT3 over 24 h in PBMCs from a group of four SS/MF patients. 18 In contrast, an earlier study documented strong expression of pSTAT3 in only 2 out of 14 SS patients.…”
Section: Discussionsupporting
confidence: 82%
“…The SOCS family of negative STAT regulators is also unlikely to mediate aberrant STAT3 activation in SS, as it has been reported that SOCS3 is expressed at high levels in CTCL cell lines and SS patients. 19 Moreover, the use of a dominantnegative STAT3 in CTCL cell lines was shown to downregulate constitutive expression of SOCS3, demonstrating that SOCS3 expression is a consequence rather than a mediator of aberrant STAT3 activation. Furthermore, no SOCS3-associated mutations have been identified in CTCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In later stages of the disease, the malignant T cells show aberrant hyperactivation of Janus kinase-3 (Jak3) 10 and signal tranducers and activators of transcription (STAT) 11,12 proteins, which in turn trigger survival signals and the expression of suppressor of cytokine signalling-3 (SOCS3). 13 SOCS3 protects the malignant T cells from inhibition by IFNs 13 and is a marker of a poor prognosis. 14 During disease progression, the normal T-cell compartment is depleted and the immune system becomes increasingly compromised, leading to a state of immunodeficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent expression of SOCS1 and/or SOCS3 is observed in several haematological malignancies. Such as cutaneous T cell lymphoma, chronic myeloid leukemia, ALK+ anaplastic large cell lymphoma and some acute leukemia (Schuringa et al, 2000;Brender et al, 2001;Sakai et al, 2002;Cho-Vega et al, 2004;Roman-Gomaz et al, 2004). Also, in patients with colorectal cancer, papillary thyroid cancer, glioblastoma primary tissues, breast cancer and hepatocellular carcinoma tumors protein expression of SOCS1 and SOCS3 (Sasi et al, 2010;Wu et al, 2011;Ayyildiz et al, 2014;Kobawala et al, 2017).…”
Section: Discussionmentioning
confidence: 99%